2011
DOI: 10.3892/ijo.2011.1133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish oil and Tamoxifen on preneoplastic lesion development and biomarkers of oxidative stress in the early stages of N-methyl-N-nitrosourea-induced rat mammary carcinogenesis

Abstract: Abstract. Epidemiologic studies on the protective role of omega-3 fatty acids (n:3) on breast cancer prevention remain inconclusive but studies in preclinical models provide more positive outcome. However, the mechanisms accounting for the protective effect of n:3 are not defined. In the present study, conducted in the N-methyl-N-nitrosourea-induced rat mammary carcinogenesis model, we examined the effects of n:3 individually and in combination with the anti-estrogen Tamoxifen (Tam) on a comprehensive panel of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…We believe that a major attractive feature of this approach is its safety since it allows us to combine a lower and hence less toxic dose of antiestrogens with n-3FA, compounds that are known to have inherent health benefits (that is, reduction in cardiovascular risk) beyond their potential chemopreventive benefit in breast cancer. 14 In parallel with our preclinical studies conducted in experimental models of mammary carcinogenesis, [2][3][4] we have recently initiated a randomized clinical trial in postmenopausal women (NCT00723398) testing the combined effects of Lovaza and Ral at half its conventional dose (that is, 30 vs 60 mg) in reducing breast density, a well-established risk factor for breast cancer. The effects of this treatment combination will be compared with that of Ral alone at its conventional dose of 60 mg daily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that a major attractive feature of this approach is its safety since it allows us to combine a lower and hence less toxic dose of antiestrogens with n-3FA, compounds that are known to have inherent health benefits (that is, reduction in cardiovascular risk) beyond their potential chemopreventive benefit in breast cancer. 14 In parallel with our preclinical studies conducted in experimental models of mammary carcinogenesis, [2][3][4] we have recently initiated a randomized clinical trial in postmenopausal women (NCT00723398) testing the combined effects of Lovaza and Ral at half its conventional dose (that is, 30 vs 60 mg) in reducing breast density, a well-established risk factor for breast cancer. The effects of this treatment combination will be compared with that of Ral alone at its conventional dose of 60 mg daily.…”
Section: Discussionmentioning
confidence: 99%
“…1 While basic mechanisms are under investigation using preclinical models of mammary carcinogenesis, [2][3][4] we are testing concomitantly the clinical relevance of this approach in postmenopausal women using surrogate markers of breast cancer development (NCT00723398). While the primary end point of our clinical trial is a reduction in breast density, a wellestablished risk factor for breast cancer, 5 we are also examining the effects of the individual and combined administration of Ral and n-3FA on several biomarkers thought to be potentially involved in mammary carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Using a prepubertal model of 1‐methyl‐1‐nitrosourea (MNU)‐induced rat mammary carcinogenesis, we have previously reported that a high fish oil (FO) diet, rich in n‐3FA, while having a marginal protective effect of its own, potentiated the chemopreventive action of the antiestrogen Tam . This experimental system, however, does not allow us to clearly define the effects of our interventions on the early stages of carcinogenesis because of the confounding influence of the concomitant physiologic changes of the mammary gland associated with puberty as previously reported by us in this model . Thus, it remains unclear which stages of breast cancer development are inhibited by the combination of n‐3FA and Tam.…”
mentioning
confidence: 98%
“…An effect of ω-3 PUFAs on the development and progression of hormone insensitive tumors was explored in a series of studies by Manni and colleagues [28–30]. The investigators hypothesized that the combination of tamoxifen and ω-3 PUFAs, which are known PPAR agonists, would prevent the development of ER-negative tumors via suppression of synergistic interactions between the ER and PPARγ pathways.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
“…However, in a subsequent study utilizing a different animal model of ER-negative breast tumors, fish oil feeding did not provide an additive protective effect when combined with tamoxifen [29]. In order to better isolate a preventive effect, the investigators next examined the effect of tamoxifen and fish oil on pre-malignant, hyperplastic lesions in their carcinogen-induced rat mammary tumor model [30]. While fish oil-feeding significantly diminished the proliferative marker, Ki-67, in the hyperplastic lesions, the development of these preneoplastic lesions was not inhibited.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%